2013
DOI: 10.1242/jcs.096701
|View full text |Cite
|
Sign up to set email alerts
|

Controlling DNA replication origins in response to DNA damage – inhibit globally, activate locally

Abstract: Summary DNA replication in eukaryotic cells initiates from multiple replication origins that are distributed throughout the genome. Coordinating the usage of these origins is crucial to ensure complete and timely replication of the entire genome precisely once in each cell cycle. Replication origins fire according to a cell-type-specific temporal programme, which is established in the G1 phase of each cell cycle. In response to conditions causing the slowing or stalling of DNA replication forks, the programme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
98
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(104 citation statements)
references
References 131 publications
(157 reference statements)
3
98
0
1
Order By: Relevance
“…(i) In general, DRC mutants (e.g., mrc1⌬) are specifically sensitive to HU, while DDC mutants (e.g., rad9⌬) are specifically sensitive to MMS (4,10,46). In the absence of either chemical, the mcm2DENQ mutant exhibited a nearly normal colony size.…”
Section: Resultsmentioning
confidence: 99%
“…(i) In general, DRC mutants (e.g., mrc1⌬) are specifically sensitive to HU, while DDC mutants (e.g., rad9⌬) are specifically sensitive to MMS (4,10,46). In the absence of either chemical, the mcm2DENQ mutant exhibited a nearly normal colony size.…”
Section: Resultsmentioning
confidence: 99%
“…Pob3-Q308K protein is stable at 37° ( VanDemark et al 2008), so the temperature sensitivity must result from unmet demand for FACT activity at elevated temperatures. HU inhibits ribonucleotide reductase (RNR), presumably causing a shortage of dNTPs and thereby stressing replication progression (Aparicio 2013;Yekezare et al 2013). Strains with the pob3-Q308K mutation are able to induce transcription of RNR genes normally (Biswas et al 2008), so the HU sensitivity (HUs) caused by this allele is interpreted as a defect in replication fork progression or checkpoint signaling.…”
Section: Pob3-q308k Defects Can Be Suppressed By Mutating H3 or H4mentioning
confidence: 99%
“…The histone mutations only partially restore FACT function, and this is sufficient to reverse the Ts 2 and HUs phenotypes, but not to reverse the Spt 2 phenotype. In one potential scenario, the Ts 2 and HU phenotypes could reveal a need for FACT activity at 400 replication forks during DNA replication (Yekezare et al 2013), which is an essential cell cycle event but one that occurs only periodically. In contrast, the Spt 2 phenotype might reveal the need to maintain a repressive chromatin state simultaneously in all regions of the genome during all cell cycle phases, and might therefore have more stringent requirements for FACT function.…”
Section: Integration Of Suppressor Mutations Into the Genomementioning
confidence: 99%
“…However, MCM2-7 complexes are recruited in excess so that not all MCM2-7 complexes are activated during a cell cycle ( Figure 1). The choice of the origins to be activated (around 30,000 in mammalian cells) is variable from cell to cell and ensures flexibility in origin usage during the DNA replication program to adapt with cell fate commitment, cell environment, and replicative stress 22, 23 . Origin mapping strategies coupled with high-throughput sequencing revealed that the chromatin context influences origin selection through genetic and epigenetic features located in close proximity to the origins.…”
Section: Coordination Between Replication Origin Licensing and G 1 Lementioning
confidence: 99%